The simulation of heat transfers and flow characterization on wickless loop heat pipe - Ainur Rosidi; Giarno Giarno; Dedy Haryanto; Nursinta Adi wahanani; Yoyok Dwi Setyo Pambudi; Mukhsinun Hadi Kusuma (Politeknik Negeri Lhokseumawe, 2022)
The severe accident at a nuclear power plant in Japan became an important lesson for aggressively involving passive cooling systems to improve safety. One of the passive cooling system technologies with excellent heat dissipation capabilities and great potential for a passive cooling system is the heat pipe, including the loop heat pipe (LHP). This research aims to study the phenomenon of heat transfer and flow characterization in the wickless loop heat pipe. The method used in this research is a simulation using the software Computational Fluid Dynamics, Fluent. This simulation study gives the effect of filling ratio and heat load in the evaporator at LHP. Demineralized water as the working fluid filled in the LHP was varied at the filling ratio values of 40%, 60%, and 80%. The heat load in the hot water temperature absorbed by the evaporator was varied by 45°C, 55°C, and 65°C. Cooling air as a heat taker in the condenser is given at a fixed temperature value of 25oC. The simulation results obtained indicate that the heat transfer in the wickless LHP has a temperature distribution profile in the LHP, which is almost uniform for every variation of filling ratio and heat load. Compared to filling ratios of 40% and 60%, at 80% filling ratios, the optimal time for the formation of natural circulation flow is achieved when the LHP is given a heat load of 55°C in the evaporator. This simulation shows that the LHP without wick does not produce an excellent natural circulation flow as expected in general natural circulation in the LHP. The results of this simulation can be used as the knowledge that the LHP that will be designed for experimental purposes must be using a wick as a vapor regulator to rise to the condenser only through one adiabatic side.